2011
DOI: 10.1108/03068291111091981
|View full text |Cite
|
Sign up to set email alerts
|

Employment situation of women in Pakistan

Abstract: PurposeThis paper is an attempt to analyze the study of low female work participation rate in Pakistan due to the religious, traditional, cultural values, the colonial ideology and the evolution of social institution that restrain women entry into the labour market.Design/methodology/approachIn order to explore the objectives, the paper develops the classification of male and female age groups into three main categories, and analyze with the help of descriptive and mean methodology.FindingsThe findings of this… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
42
0

Year Published

2011
2011
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 59 publications
(44 citation statements)
references
References 9 publications
2
42
0
Order By: Relevance
“…As the findings reported above illustrate, cultural, national and religious contexts set the parameters within which women are encouraged to define their role and worth in relation to men and elder generations. Women's education and employment opportunities, social welfare support and childcare provision all influence their economic positioning (Dale & Ahmed, 2011;Kishor & Gupta, 2009;Sadaquat & Sheikh, 2011) and so the strategies they use to respond to and/or resist economic abuse. Further, a crucial element in women's response to economic abuse is their access to statutory and South Asian women's narratives of economic abuse 25 voluntary services.…”
Section: Discussionmentioning
confidence: 99%
“…As the findings reported above illustrate, cultural, national and religious contexts set the parameters within which women are encouraged to define their role and worth in relation to men and elder generations. Women's education and employment opportunities, social welfare support and childcare provision all influence their economic positioning (Dale & Ahmed, 2011;Kishor & Gupta, 2009;Sadaquat & Sheikh, 2011) and so the strategies they use to respond to and/or resist economic abuse. Further, a crucial element in women's response to economic abuse is their access to statutory and South Asian women's narratives of economic abuse 25 voluntary services.…”
Section: Discussionmentioning
confidence: 99%
“…We relied on these midwives to collect data for this study (27,28). HANDS shoulders the responsibility for health facilities in two of the towns (Gadap and Bin Qasim), and has established 10 health field sites in these towns (17,18). For this study, six of these sites were randomly chosen for data collection.…”
Section: Study Design and Populationmentioning
confidence: 99%
“…Pakistan is a low-income Muslim country with approximately 176 million inhabitants. Only 36 % of the women can read and write, and the employment rate for women is 22.2 %, as compared with an average of 77.8 % for men, with higher rates in urban areas (17,18). The Pakistani society is male dominated, and the majority of women have to accept arranged marriages; further married women have to accept a certain degree of partner violence to secure the marriage and avoid social stigma (10).…”
Section: Introductionmentioning
confidence: 99%
“…The Bangladesh Home Workers Women's Association (BHWA) revealed that the estimated annual contribution of home-based workers to GDP is about TK.150 billion (Islam, 2006). Some studies have pointed out that men do not even appreciate women's household work in Bangladesh or their economic activities (Mehra, 1997;Sen, 1997;Bhatt, 1989;Efroymson et al, 2006;Sadaquat and Sheikh, 2011). In the 1961 Census, women's household work was defined as "productive economic activity" but in the 1974 Census (the First Census after independence in 1971) women's household work was defined as "housewife" (Waring, 1998).…”
Section: Nature Of Women's Economic Activities In Bangladeshmentioning
confidence: 99%